2020
DOI: 10.1101/2020.02.07.20020727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial inequality hides the burden of dog bites and the risk of dog-mediated human rabies

Abstract: Currently, there is an active rabies outbreak in the dog population of Arequipa, Peru. Inhabitants of the city are bitten by both pets and free-roaming dogs; therefore, the risk of human rabies transmission is concerning. Our objective was to estimate the rate of dog bites in the city and to identify factors associated with going or not going to a medical facility for rabies follow-up. To this end, we conducted a door-to-door survey of 4,000 houses in 21 urban and 21 peri-urban communities. We then analyzed as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Most barriers expressed by participants could be compounded by distance to the nearest health center. In a recent study, our group found that, on average, peri-urban houses are further away from health facilities [37]. Finally, FGD participants from both areas suggested there should be more information about human rabies on television, including people's testimonies, to improve dissemination about disease prevention.…”
Section: Facilitator: Even Though They Can Die?mentioning
confidence: 83%
“…Most barriers expressed by participants could be compounded by distance to the nearest health center. In a recent study, our group found that, on average, peri-urban houses are further away from health facilities [37]. Finally, FGD participants from both areas suggested there should be more information about human rabies on television, including people's testimonies, to improve dissemination about disease prevention.…”
Section: Facilitator: Even Though They Can Die?mentioning
confidence: 83%
“…Our results show that stopping or pausing dog vaccination and rabies surveillance during the COVID-19 pandemic will substantially increase the number of cases of canine rabies with an associated increased risk of human rabies within a few months. The lockdowns have the potential to reduce contact between rabid dogs and humans, but essential activities and some measures to reactivate the economy require people to leave their houses in a city with the highest rate of dog bites in Latin America (42). This model is a logical tool to clarify trends that may result from neglect of rabies due to COVID-19 (as opposed to a tool to predict exact numbers of infected dogs on specific dates).…”
Section: Discussionmentioning
confidence: 99%
“…In a study published in this issue of the American Journal of Tropical Medicine and Hygiene , De la Puente-León and others 5 studied the population of Arequipa, Peru, one of the pockets of rabies reintroduction in dogs. Through interviews in urban and peri-urban areas of the city, which have very different economic and social arrangements, the study sought to quantify the extent of dog bites and to characterize factors linked to healthcare-seeking behaviors.…”
mentioning
confidence: 99%